How to maintain sustainability of micro and small entreprises of crispy oil palm mushroom: A case study in Riau Province. Issue 2 (11th December 2018) - , Caska; Indrawati, Henny
Abstract : Purpose: This paper aims to analyze sustainability level of crispy palm tankos mushroom business; institutions involved in the development of crispy palm tankos mushroom business in Riau Region; nutritional composition, sensory assessment both descriptively and hedonically, and also designing the suitable and hygienic packaging for crispy palm tankos mushroom in Riau; institutional structuring model involved in the development of crispy palm tankos mushroom business in Riau; and strategies to improve the quality of crispy palm tankos mushroom in Riau. Design/methodology/approach: This study is quantitative research conducted by survey. The research was conducted in Indragiri Hulu, Pelalawan, Kampar and Siak, Riau Province, Indonesia from April to August 2017. The study population is all producers producing crispy oil palm mushroom in the research area. The sample was determined purposively with the criterion of the producers who have been running their business for at least 5 years. Based on the criterion, there were 225 producers included as the sample. Findings: This study found that business sustainability is the main concern of micro business of crispy palm tankos mushroom in Riau Province. Although local government lack of support, the average value of business sustainability is in the very high category. In addition due to the excellent business support quality, business sustainability is supported by the family environment, independence and business progress. There are two institutions involved in the development of makers business to date, they are informal financial institutions that help makers to increase business capital, and retailers who help makers deliver products to consumers. The results of nutritional composition analysis of crispy palm tankos mushroom showed that the crispy tankos mushroom is a product with good nutrition value for consumption by the community. The implication of this study is to improve the quality of the tankos mushroom crispy palm in terms of color according to the choice of the panelists. Originality/value: Originality of this study aims to provide strategic formulation to use local resources and improve the economic actors of the home industry of crispy palm tankos mushroom processing in Riau. This research is conducting a structure to the institutions involved in the development of crispy palm tankos mushroom and improving the product quality. This research contributes to the development of science, especially economic development, particularly the development of small industries.